Tecnology, environment and interactions in health promotion to the newborn and his family - Márcia Maria Coelho Oliveira; Andréa Lopes Barbosa; Marli Teresinha Gimeniz Galvão; Maria Vera Lúcia Moreira Leitão Cardoso (Rev Rene)
It is a case study developed into a qualitative approach aiming to analyze the environmental cares and interactions between nursing team, hospitalized premature newborn and his family as strategies to health promotion in a Neonatal Intensive Care Unit (NICU), in Fortaleza, Ceará. On June 2008, as data collection it was used the observation of the nursing care to newborn and the registers from patient chart. As for analysis, were created three categories, which emmerged from articulations established between the fundamentals of the interactions: professional/baby, professional/relatives and professional/ binomial mother baby. It was so concluded that in such environment, the professional must be in harmony with the baby, mother and hospital team. On the other hand, the technological evolution influences the environment and the professional know how to do, being possible to accomplish practices of health promotion in the critics units, offering human and individualized quality attention, to newborns and their relatives.